Hubungan Simtom Depresi dengan Kualitas Hidup Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisis di RSUD Drs. H. Amri Tambunan: Hubungan Simtom Depresi dengan Kualitas Hidup Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisis di RSUD Drs. H. Amri Tambunan - Pohan, Muhammad Alwi; Tambunan, Asri Ludin; Nuralita, Nanda Sari; Chaniago, Lita Septina (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2024)
Background: Chronic kidney disease is a disease that occurs as a result of structural and functional kidney damage that lasts for more than three months with a glomerular filtration rate (GFR) or Glomerular Filtration Rate (GFR) of less than 60mL/min/1.73 m2. The prevalence of kidney failure in Indonesia increases every year, to treat it requires kidney replacement therapy, one of which is hemodialysis which must be done for life. Hemodialysis therapy is a substitute for kidney function to remove metabolic waste or certain toxins from human blood circulation which aims to remove fluids, electrolytes and metabolic waste from the body, thereby indirectly extending the patient's life. Objective: To determine the relationship between depression and the quality of life of chronic kidney disease patients undergoing hemodialysis at Drs. H. Amri Tambunan. Population: The population in this study were patients with chronic kidney disease undergoing hemodialysis at the hemodialysis unit of RSUD Drs. H. Amri Tambunan. The number of research samples is 40 people. Method: The type of research used is categorical correlative analytic in RSUD Drs. H. Amri Tambunan. This study used a cross-sectional design. The research instrument used the KDQOL-SF and BDI which were analyzed using the Spearman test. Results: Kidney disease patients undergoing hemodialysis at Drs. H. Amri Tambunan did not experience depression as many as 22 respondents (55.0%) while the quality of life was mostly in the category of moderate quality of life as many as 22 people (55.0%). Conclusion: After the spearment statistical test was carried out, a significant value or sig (2-tailed) of 0.001 was obtained which showed that there was a relationship between depressive symptoms and the quality of life of chronic kidney disease patients undergoing hemodialysis at Drs. H. Amri Tambunan. The correlation coefficient value was 0.524 which indicated that there was a strong relationship between depressive symptoms and the quality of life of chronic kidney disease patients undergoing hemodialysis at Drs. H. Amri Tambunan. The correlation coefficient is negative, namely -0.524, so the relationship between the two variables is not unidirectional.Thus it can be interpreted that the higher the symptoms of depression, the level of quality of life will decrease.